All Days 2014
DOI: 10.4043/24690-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Placement Approach for Chemical Sand and Fines Control Using Zeta Potential Altering Chemistry

Abstract: Sand and fines production is one of the oldest problems in petroleum industry and one of the toughest to solve. Today, many active and passive technologies and methods exist; in some cases some sand and fines production is manageable, while for others it cannot be tolerated at all. Also, many wells do not produce sand or fines from the onset and may not require an active sand control solution until later in their live. Chemical sand control solutions have been around for many years have always been attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Habibi et al performed experiments with three types of NPs, MgO, Al 2 O 3 , and SiO 2 , and found that MgO NPs were the most effective in stabilizing fines. For the ZPAS, the effective constituent is an inner salt of a low-molecular-weight polymer that can alter surface potentials to an optimum range from −20 to +20 mV, thus making for a stronger attraction between fines and the fracture surface . In addition, the STA polymer is a high-molecular-weight, hydrophilic polyamide, onto which hydrophobes are grafted.…”
Section: Implications For Field-scale Fines Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Habibi et al performed experiments with three types of NPs, MgO, Al 2 O 3 , and SiO 2 , and found that MgO NPs were the most effective in stabilizing fines. For the ZPAS, the effective constituent is an inner salt of a low-molecular-weight polymer that can alter surface potentials to an optimum range from −20 to +20 mV, thus making for a stronger attraction between fines and the fracture surface . In addition, the STA polymer is a high-molecular-weight, hydrophilic polyamide, onto which hydrophobes are grafted.…”
Section: Implications For Field-scale Fines Controlmentioning
confidence: 99%
“…Due to hydrophobe interactions through VDW bonds, a strong molecular hook-and-latch system is formed between fines and the fracture surface, thus providing an increased adhesive force . Several experimental and field studies have demonstrated that chemical methods successfully prevent fines migration, even under high flow rates and flow interruptions, with no observed reduction in permeability. …”
Section: Implications For Field-scale Fines Controlmentioning
confidence: 99%
See 1 more Smart Citation